Odontoglossum crispum: a tale of love, loss and scientific discovery - Seaton, Philip T. (Universidad de Costa Rica, 2023)
This is the story of Odontoglossum crispum (Oncidium alexandrae) (Bateman) M.W.Chase & N.H.Williams, from the 19th century to the present day. It is a love story because Odontoglossum crispum was considered by many to be the most beautiful of all orchid species. It was collected by the hundreds of thousands from the cloud forests of its native Colombia and exported to Britain, the rest of Europe and the USA. Vast numbers were lost in transit. When they arrived many perished due to a lack of understanding of its needs in cultivation. Only the ‘best’ forms were grown, and the remainder discarded. Today much of its native habitat has either disappeared or been despoiled due to human actions. Few plants remain in cultivation in the UK. It was one of the first species to be grown commercially from seed, most notably in the UK by Charlesworth & Co., following the scientific discovery by Noël Bernard that orchid seeds required the participation of a suitable fungus to germinate under natural conditions.